Induction of systemic antitumour resistance with targeted polymers - Rihova, B; Strohalm, J; Kovar, M; Mrkvan, T; Subr, V; Hovorka, O; Sirova, M; Rozprimova, L; Kubackova, K; Ulbrich, K (Scandinavian journal of immunology, 2005)
Conjugates based on N-(2-hydroxypropyl)methacrylamide (HPMA) represent a new generation of antibody-targeted polymeric anticancer drugs with both cytotoxic and immunoprotecting/immunomobilizing activity. 20-90% of mice that are cured of EL4 mouse T-cell lymphoma, BCL1 mouse B-cell leukaemia and 38C13 mouse B-cell lymphoma by injection of doxorubicin-HPMA conjugate develop a long-lasting memory and systemic antitumour resistance. It is suggested that the main activity of the polymeric drug, directly after application is - due to the high level of the drug - of cytotoxic and cytostatic nature. Thereafter, long-term conjugates persist at low concentration in the circulation, which are capable of mobilizing the defence mechanisms of the host. Until now, seven patients with generalized carcinoma were treated with doxorubicin-HPMA-human-Ig conjugate. Disease stabilization, lasting from 6 to more than 18 months, was recorded.
Keywords: přirozená imunita; Neoplasms; Doxorubicin; Methacrylates; doxorubicin; protinádorová antibiotika; zvířata; Humans; Antibiotics, Antineoplastic; methakryláty; nádory; Immunity, Innate; lidé; Animals